Impact of the municipal waste collection system in cities on urban space and the functioning of their inhabitants - Kleszcz, Justyna; Maciejko, Alicja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article looks at the latest trends in solving the problem of garbage collection, segregation and disposal in urban housing estates in the scope of design, architectural and spatial solutions. The paper adopts a method of analysing existing applications in view of globally shifting living conditions. As a result of the conducted analyses, a set of features and factors was singled out, ranging from functional-spatial, through transport and ergonomic to social and aesthetic ones. Also, conclusions that should be taken into account when determining the principles for designing these structures were presented.
Keywords: municipal waste; waste segregation; street furniture; garbage; trash; waste collection system; odpady miejskie; segregacja odpadów; odpady wielkogabarytowe; śmieci; wiata śmietnikowa; system zbierania odpadów